The Archaeology of Europe's Drowned Landscapes - Bailey, Geoff; Galanidou, Nena; Peeters, Hans; Jöns, Hauke; Mennenga, Moritz (Coastal Research Library,, 2020)
This open access volume provides for the first time a comprehensive description and scientific evaluation of underwater archaeological finds referring to human occupation of the continental shelf around the coastlines of Europe and the Mediterranean when sea levels were lower than present. These are the largest body of underwater finds worldwide, amounting to over 2500 find spots, ranging from individual stone tools to underwater villages with unique conditions of preservation. The material reviewed here ranges in date from the Lower Palaeolithic period to the Bronze Age and covers 20 countries bordering all the major marine basins from the Atlantic coasts of Ireland and Norway to the Black Sea, and from the western Baltic to the eastern Mediterranean. The finds from each country are presented in their archaeological context, with information on the history of discovery, conditions of preservation and visibility, their relationship to regional changes in sea-level and coastal geomorphology, and the institutional arrangements for their investigation and protection. Editorial introductions summarise the findings from each of the major marine basins. There is also a final section with extensive discussion of the historical background and the legal and regulatory frameworks that inform the management of the underwater cultural heritage and collaboration between offshore industries, archaeologists and government agencies. The volume is based on the work of COST Action TD0902 SPLASHCOS, a multi-disciplinary and multi-national research network supported by the EU-funded COST organisation (European Cooperation in Science and Technology). The primary readership is research and professional archaeologists, marine and Quaternary scientists, cultural-heritage managers, commercial and governmental organisations, policy makers, and all those with an interest in the sea floor of the continental shelf and the human impact of changes in climate, sea-level and coastal geomorphology.